LRP10 genetic variants in familial Parkinson's disease and dementia with Lewy bodies: a genome-wide linkage and sequencing study. Issue 7 (July 2018) - Quadri, Marialuisa; Mandemakers, Wim; Grochowska, Martyna M; Masius, Roy; Geut, Hanneke; Fabrizio, Edito; Breedveld, Guido J; Kuipers, Demy; Minneboo, Michelle; Vergouw, Leonie J M; Carreras Mascaro, Ana; Yonova-Doing, Ekaterina; et al.
Summary: Background: Most patients with Parkinson's disease, Parkinson's disease dementia, and dementia with Lewy bodies do not carry mutations in known disease-causing genes. The aim of this study was to identify a novel gene implicated in the development of these disorders. Methods: Our study was done in three stages. First, we did genome-wide linkage analysis of an Italian family with dominantly inherited Parkinson's disease to identify the disease locus. Second, we sequenced the candidate gene in an international multicentre series of unrelated probands who were diagnosed either clinically or pathologically with Parkinson's disease, Parkinson's disease dementia, or dementia with Lewy bodies. As a control, we used gene sequencing data from individuals with abdominal aortic aneurysms (who were not examined neurologically). Third, we enrolled an independent series of patients diagnosed clinically with Parkinson's disease and controls with no signs or family history of Parkinson's disease, Parkinson's disease dementia, or dementia with Lewy bodies from centres in Portugal, Sardinia, and Taiwan, and screened them for specific variants. We also did mRNA and brain pathology studies in three patients from the international multicentre series carrying disease-associated variants, and we did functional protein studies in in-vitro models, including neurons from induced pluripotent stem-like cells. Findings: Molecular studies were done between Jan 1, 2008, and Dec 31, 2017. In the initial kindred of ten affected Italian individuals (mean age of disease onset 59·8 years [SD 8·7]), we detected significant linkage of Parkinson's disease to chromosome 14 and nominated LRP10 as the disease-causing gene. Among the international series of 660 probands, we identified eight individuals (four with Parkinson's disease, two with Parkinson's disease dementia, and two with dementia with Lewy bodies) who carried different, rare, potentially pathogenic LRP10 variants; one carrier was found among 645 controls with abdominal aortic aneurysms. In the independent series, two of these eight variants were detected in three additional Parkinson's disease probands (two from Sardinia and one from Taiwan) but in none of the controls. Of the 11 probands from the international and independent cohorts with LRP10 variants, ten had a positive family history of disease and DNA was available from ten affected relatives (in seven of these families). The LRP10 variants were present in nine of these ten relatives, providing independent—albeit limited—evidence of co-segregation with disease. Post-mortem studies in three patients carrying distinct LRP10 variants showed severe Lewy body pathology. Of nine variants identified in total (one in the initial family and eight in stage 2), three severely affected LRP10 expression and mRNA stability (1424+5delG, 1424+5G→A, and Ala212Serfs*17, shown by cDNA analysis), four affected protein stability (Tyr307Asn, Gly603Arg, Arg235Cys, and Pro699Ser, shown by cycloheximide-chase experiments), and two affected protein localisation (Asn517del and Arg533Leu; shown by immunocytochemistry), pointing to loss of LRP10 function as a common pathogenic mechanism. Interpretation: Our findings implicate LRP10 gene defects in the development of inherited forms of α-synucleinopathies. Future elucidation of the function of the LRP10 protein and pathways could offer novel insights into mechanisms, biomarkers, and therapeutic targets. Funding: Stichting ParkinsonFonds, Dorpmans-Wigmans Stichting, Erasmus Medical Center, ZonMw—Memorabel programme, EU Joint Programme Neurodegenerative Disease Research (JPND), Parkinson's UK, Avtal om Läkarutbildning och Forskning (ALF) and Parkinsonfonden (Sweden), Lijf and Leven foundation, and cross-border grant of Alzheimer Netherlands–Ligue Européene Contre la Maladie d'Alzheimer (LECMA).